Maggie finds her muse - Ernst, Dee (St. Martin's Griffin, 2021)
"All Maggie Bliss needs to do is write. Forty-eight years old and newly single (again!), she ventures to Paris in a last-ditch effort to finish her manuscript. With a marvelous apartment at her fingertips and an elegant housekeeper to meet her every need, a finished book--and her dream of finally taking her career over the top--is surely within her grasp. After all, how could she find anything except inspiration in Paris, with its sophistication, food, and romance in the air? But the clock is running out, and between her charming ex-husband arriving in France for vacation and a handsome Frenchman appearing one morning in her bathtub, Maggie's previously undisturbed peace goes by the wayside."--Provided by publisher.